Return on investment in corporate responsibility - Saenz Acosta, Cesar (Emerald points., 2018)
In today's climate, companies must be economically successful and at the same time take social responsibility. Author Cesar Sandro Saenz Acosta introduces a new SROIM (Social Return on Investment Management) model, to design and measure the social value created by companies. SROIM is a framework for tracking, understanding, measuring, and reporting the social, economic and environmental value created by a project, a program, or a business. This value creation can be done: during design and development, to plan for maximum value; during implementation, so that maximum value can be attained; during post-analysis, to assess the delivered value against the anticipated value. Acosta presents a methodological approach that can be replicated throughout an organization, to demonstrate a company's creation of value through the social return of the investment.